The Effectiveness of Non-Custodial Sanctions in Juvenile Justice: An Empirical Study on the Implementation of Restorative Justice in Bengkulu - Sitepu, Sudirman; Fernando, Zico Junius; Sary, Wevy Efticha; Taniady, Vicko (Journal of Judicial Review, 2025)
This study examines the effectiveness of non-custodial sanctions within Indonesia’s juvenile justice system, with a particular focus on the implementation of restorative justice in Bengkulu Province. Grounded in Law No. 11 of 2012 on the Juvenile Criminal Justice System (UU SPPA) and international instruments such as the CRC and Tokyo Rules, the research explores the normative, institutional, and empirical dimensions of diversion and community-based sanctions for children in conflict with the law. Adopting a socio-legal methodology, the study combines doctrinal analysis with qualitative fieldwork involving 25 semi-structured interviews with judges, prosecutors, police investigators, correctional officers, and community leaders, complemented by direct observations of diversion sessions and the analysis of court and institutional documents. The findings reveal a strong normative commitment to restorative principles but highlight significant gaps in practice due to limited institutional capacity, inconsistent inter-agency coordination, and persistent cultural stigmas. Diversion programs in Bengkulu have demonstrated positive impacts on rehabilitation and social reintegration, particularly when supported by families and local communities. However, the absence of standardized procedures, integrated data systems, and adequate professional training undermines long-term sustainability. The study concludes that meaningful juvenile justice reform requires not only legal and procedural refinement but also transformative engagement with societal attitudes and sustained investment in supportive infrastructure. It further offers concrete policy recommendations to strengthen the restorative justice ecosystem and promote a more humane, rights-based approach to juvenile justice in Indonesia.